(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Chronic catarrhal gingivitis (CCG) is a widespread inflammatory condition of the gums, often resulting from poor oral hygiene and exacerbated by systemic factors. Recent research has indicated that helminth infections—parasitic infestations affecting millions worldwide—may worsen oral health by modulating systemic inflammation and immune responses. This article reviews the challenges of treating CCG in patients with concurrent helminthiasis and proposes integrated treatment approaches that combine traditional oral care with targeted antiparasitic therapy. By addressing both local and systemic contributors to the disease, these strategies aim to enhance patient outcomes and reduce recurrence rates.